Peran Strategi Bisnis Fintech Payment Gateway dalam Meningkatkan Kinerja UMKM di NTB - Armiani Armiani; Dwi Arini Nursansiwi (Owner : Riset dan Jurnal Akuntansi, 2023)
Presidency Group of Twenty (G20) strengthen the acceleration of the digital transformation agenda, in line with the government's goal of national economic recovery after the Covid-19 pandemic. MSME actors are required to adapt in order to be able to be competitive in improving company performance for the sake of business sustainability. This study aims to identify fintech payment gateway becoming a business strategy in improving the performance of MSMEs in NTB. The method approach adopted in this study is qualitative with a case study description. Data were obtained through observation and interviews with 12 (twelve) informants, with the criteria; 1). MSME actors who use the application fintech, 2). Doing business online, 3). The payment system uses payment gateways, 4). MSME in NTB. The results of the study indicate that business transactions on line become a business strategy for MSME actors to improve MSME performance and business sustainability. This is because the payment system using payment gateway can transact easily, quickly, precisely, efficiently, effectively, so that actors can provide excellent service to their consumers, this is also supported and in line with the pleasures of consumers from the millennial generation and generation Z, which are dominant in transactions using fintech and saving money using E-wallet, so that consumers prefer to transact online on line with a payment system using payment gateway.